Anemia and Its Associated Factors among Final-Year Medical Students at Sana'a University, Yemen - Mogahid Y. Nassar; Ahmed S. Hudna; Fatima Abdurubbu; Aisha Mohammed; Ala'a Maresh; Fatima Mohammed; Hadeer Al-ariqi; Reem Al-maqtari; Narmeen Al-ariqi; Wafa'a Al-hammadi (University of Science and Technology, Sana'a, 2021)
Objective: To determine the prevalence of anemia and its associated risk factors among final-year medical students at Sana'a University, Yemen. Methods: This cross-sectional study was conducted among 269 final year students randomly selected from the medical faculties of Sana'a University in the period from January to April 2018. Data were collected using a structured questionnaire, while venous blood samples were collected by venipuncture into EDTA tubes. Hemoglobin (Hb) concentration was estimated using an automated hematology analyzer in the Laboratory Department of the University of Science and Technology in Sanaa city. Data were analyzed using appropriate statistical tests, and statistical significance was considered at P-values <0.05. Results: The mean Hb concentration of final-year medical students at Sanaa University was 15.1 1.9 g/dL. The mean Hb concentration for male students was 16.3 1.5 g/dL, while the mean Hb concentration for female students was 13.1 1.5 g/dL. Anemia was prevalent among 12 (4.5%) out of 269 medical students and was significantly associated with the gender and smoking status of the students, where females (OR = 5.9, 95% CI: 1.827.4; P = 0.011) and smokers (OR = 6.3, 95% CI: 1.23.7; P = 0.002) were about six times more likely to be anemic compared to their counterparts. In contrast, there was no statistically significant association between anemia and age, family size, family income, presence of chronic disease(s), khat chewing, exercise, or history of blood transfusion. Conclusions: The prevalence of anemia among final-year medical students at Sana'a University is low compared to other studies elsewhere. The female gender and smoking are the risk factors significantly associated with anemia among medical students. Further large-scale studies among medical and non-medical students from different levels of study at public and private universities of the country are recommended.